A phylogeographic pattern of the trans-Palaearctic littoral water flea Pleuroхus truncatus (O.F. Müller, 1785) (Cladocera: Chydoridae) - Alexey A. Kotov; Petr G. Garibian; Anna N. Neretina; Dmitry P. Karabanov (PeerJ)
Water fleas (Crustacea: Cladocera) are recently regarded as models for phylogeographic studies, but most such publications are concerned the planktonic genera, first of all, Daphnia O.F. Müller. The aim of our article is to study the phylogeographic pattern of a very common littoral chydorid Pleuroxus truncatus (O.F. Müller) based on sequences of two mitochondrial (cytochrome oxidase (COI) and 16S) and two nuclear (18S and 28S) genes. All totality of the sequences could be subdivided into two major clades, A, having a predominantly European distribution with a single exclusion, and B, having a predominantly Asian distribution, but with few populations in European Russia; the clade B is subdivided into three subclades (B1–B3) with a moderate support. Earlier derived phylogroups (subclades B1 and B2) are distributed in south portion of Western Siberia. This pattern is known for previously studied daphniids. Estimations of the major clade (A and B) and subclade differentiation time in P. truncatus based on different methods lie in the interval of ca. 0.01–0.3 Mya. Therefore, the whole revealed pattern is very young, related to Late Pleistocene and more shallow as compared to previously studied daphniids. Probably, the total population of P. truncatus was not so strongly split by the unfavorable conditions during the Pleistocene cold phases.